PERAN NORWEGIA DALAM PROSES PERDAMAIAN ANTARA GERAKAN SEPARATIS MACAN TAMIL DAN PEMERINTAHAN SRILANKA ( 2002-2010 ) - Wicakono, Digdoyo; ", Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Ethnic conflict happened in Srilanka caused of given different right form Tamil ethnic and Sinhalee ethnic on this country. This conflict has been happened since 1947 until 2003. Were Tamil ethnic is an party whose want to separate from Srilanka government. It happened because Srilanka government doesn’t give equal right to Tamil ethnic. Tamil ethnic claim that the government just gived the right just for Sinhalee ethnic. Tamil ethnic through LTTE does many ways to get the equal right from Srilanka government including doing demonstration, kipnap, robbing, gun attacks etc. Srilanka government ever do some intern peace negotiation to both party but they cannot find resolution to resolve the conflict. Finally both party intioted Norwey government to become mediator to help resolve the confict. Norwey successfully resolve the conflict by sustaining the peaceThe conflict resolution in the period 2002-2009 shows the changing in the phase of conflict resolution by the existing involvement of Norwegian as the third party in the whole process of conflict resolution, cease fire agreement, conflict symetricalisation, the formation of Sri Lanka Monitoring Mission (SLMM) and the implementation of a series of conflict negotiation round table between both parties process via economic immediate assistance and joint taks force.